Portraits of change by farmers in Southern Guinea-Bissau - Pinho, J. R. (Visual Ethnography, 2016)
This photo essay, whose images and captions were created by farmers living in Cantanhez National Park, Guinea-Bissau, illustrates and analyzes the diverse ways in which these West African photographers and collaborative researchers chose to represent change. Some of the visual and narrative devices employed by the photographers include staging the past; representing before/after situations; and thoughtful composition in the visual depiction of changed and changing physical environments. Beyond our initial research focus on perceptions of climatic changes, these farmers turned photographers shared compelling portrayals of change in its social, economic, ecological and cultural complexity, in some cases offering counter-narratives to the dominant environmentalist narrative about this protected area.